Evaluasi Peran Audit Internal Sebagai Pencegah dan Pendeteksi Fraud Pada PT XYZ - Sitorus, Heidi Ruth Corry; Fitriany, Fitriany (Dinasti Publisher, 2025)
This study aims to evaluate the role of internal audit as a fraud prevention and detector at PT XYZ, using internal control framework based on the COSO 2013 Internal Control – Integrated Framework. This study is a case study with an evaluation type, with data collection through in-depth interviews and focus group discussions with five key informants involved in the company's operations and finances. The results of the study indicate that although PT XYZ has strengthened its internal control system by recruiting internal auditors, there are weaknesses in the transaction verification procedures that allow fraud to occur. The analysis also identified the need for improvements in control activities, especially related to ongoing investigations and supervision. Based on these results, this study recommends designing a more effective internal control system by strengthening transaction document checking procedures, integrating technology-based monitoring systems, and training for internal auditors to increase effectiveness in detecting and preventing fraud. These findings are expected to be a reference for strengthening internal audit practices in similar organizations, especially in the small and medium business sector.